2017
DOI: 10.17932/iau.ijemme.21460604.2017.7/1.1335-1354
|View full text |Cite
|
Sign up to set email alerts
|

Developing of Android Mobile Application Using Java and Eclipse: An Application

Abstract: -In this work, an article has prepared which can be a guide to researchers who want to start developing Android-based applications. Android is known as an operating system that comes face to face with more than one million applications. While Android sets the ground for different applications, people are aiming for unlimited entertainment for their lives and learning while they are having fun. Mobile application development steps are described for those who want to develop a mobile app for their own business, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…It is also suggested that university students can use Java (in addition to Python, AppInvertor, Scratch, C++ tutors) to develop their own applications. The study by Kocakoyun (Kocakoyun, 2017) gives reasons why a highly qualified specialist should be able to use Java and Eclipse tools to develop mobile applications. The scholar provides detailed information on how to develop and test a mobile application and describes the steps of creating a project from scratch.…”
Section: Review Of Russian Pedagogical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It is also suggested that university students can use Java (in addition to Python, AppInvertor, Scratch, C++ tutors) to develop their own applications. The study by Kocakoyun (Kocakoyun, 2017) gives reasons why a highly qualified specialist should be able to use Java and Eclipse tools to develop mobile applications. The scholar provides detailed information on how to develop and test a mobile application and describes the steps of creating a project from scratch.…”
Section: Review Of Russian Pedagogical Literaturementioning
confidence: 99%
“…Teachers are not active enough in involving students in developing their own mobile apps to solve real-life problems (Soboleva, Perevozchikova, 2019). They give the following reasons for the existing situation: lack of time, lack of necessary knowledge and training, lack of skills of programming in appropriate environments (Cherniavskikh et al, 2019), inconsistency in the level of students' algorithmic thinking culture and complexity of a particular problem (Kocakoyun, 2017). The kind of training based on project team work has the resources to resolve these difficulties (Burgess et al, 2019).…”
Section: Introduction 1significance Of the Researchmentioning
confidence: 99%
“…Pada tahun 2017, Kocakoyun membuat aplikasi Android berbasis Java untuk diteliti [2]. Beliau mengatakan bahwa pembuatan aplikasi Android dengan menggunakan metode ini cocok untuk pemula dan mudah untuk diterapkan.…”
Section: Pendahuluanunclassified
“…Mobile devices such as smartphones and tablets have become essential in different fields, such as education [1,2], finance, travel, music and utilities [3]. The number of mobile applications available for the Android mobile devices has been smashing its own record continuously with up to a billion applications available on Google Play Store [4]. The technology of developing applications for Android mobile devices is becoming more reachable and easier to learn, and the development tools are becoming available either open source or free.…”
Section: Building Efficient Applicationsmentioning
confidence: 99%
“…Enhancing the software testing phase using AI has been an emerging field of research with numerous works done to achieve this target [4,8,[14][15][16][17][18][19]. In these works, researchers reported promising results obtained from applying AI techniques, such as genetic algorithms (GAs) to enhance the software engineering process.…”
Section: Ai In Software Engineeringmentioning
confidence: 99%